Hemangioblastoma of the Gastrointestinal Tract: A First Case. (April 2013) - Casadei Gardini, Andrea; Pieri, Federica; Fusaroli, Pietro; Oboldi, Devil; Passardi, Alessandro; Monti, Manlio; Rosetti, Paola; Calpona, Sebastiano; Valgiusti, Martina; Ragazzini, Angela; Amadori, Dino; Frassineti, Giovanni Luca
We present the first documented case of hemangioblastoma located in the left colon. A 75-year-old woman undergoing adjuvant chemotherapy for breast cancer experienced rectal bleeding. Colonoscopy revealed a roundish mass covered with normal mucosa in the sigmoid colon. Endoscopic ultrasound showed an isoechoic lesion originating from the third layer of the intestinal wall; underlying layers were normal. Endoscopic ultrasound features were not suggestive of either cancer or malignant stromal tumor. Left hemicolectomy was subsequently performed due to repeated episodes of lower gastrointestinal bleeding. Grossly, a circumscribed submucosal yellowish nodule (13 mm) was observed, which was not attached to any peripheral nerve. Histologically, the lesion was composed of large, atypical cells traversed by a network of blood vessels. Immunohistochemically, the cells showed positivity for inhibin and NSE and weak positivity for S-100. A diagnosis of hemangioblastoma was made. This case highlights that hemangioblastoma of the gastrointestinal tract can also occur.